Suprabasin as a novel tumor endothelial cell marker. Issue 12 (5th November 2014) - Alam, Mohammad T.; Nagao‐Kitamoto, Hiroko; Ohga, Noritaka; Akiyama, Kosuke; Maishi, Nako; Kawamoto, Taisuke; Shinohara, Nobuo; Taketomi, Akinobu; Shindoh, Masanobu; Hida, Yasuhiro; Hida, Kyoko
<x xml:space="preserve">Abstract</x> Recent studies have reported that stromal cells contribute to tumor progression. We previously demonstrated that tumor endothelial cells (TEC) characteristics were different from those of normal endothelial cells (NEC). Furthermore, we performed gene profile analysis in TEC and NEC, revealing that suprabasin (SBSN) was upregulated in TEC compared with NEC. However, its role in TEC is still unknown. Here we showed that SBSN expression was higher in isolated human and mouse TEC than in NEC. SBSN knockdown inhibited the migration and tube formation ability of TEC. We also showed that the AKT pathway was a downstream factor of SBSN. These findings suggest that SBSN is involved in the angiogenic potential of TEC and may be a novel TEC marker.